Correction to: The European Society of Gynaecological Oncology/European Society for Radiotherapy and Oncology/European Society of Pathology Guidelines for the Management of Patients with Cervical Cancer - Cibula, David; Pötter, Richard; Planchamp, François; Avall-Lundqvist, Elisabeth; Fischerova, Daniela; Haie-Meder, Christine; Köhler, Christhardt; Landoni, Fabio; Lax, Sigurd; Lindegaard, Jacob Christian; Mahantshetty, Umesh; Mathevet, Patrice; et al. (Virchows Archiv, 2018)
Two corrections were made to the above publication following its original online publication on 4th May 2018.